2022
DOI: 10.52711/0974-360x.2022.00880
|View full text |Cite
|
Sign up to set email alerts
|

Development and qualitative evaluation of periodontal gel containing an antibacterial agent for periodontal disease

Abstract: The present study aims at the development and evaluation of dental gel containing metronidazole non-biodegradable polymers for targeted delivery of drug and thus prolonging the action. Hot Method was used for the preparation of gel. Natural polymers like, Guar gum, Sodium alginate, Chitosan, Xanthan gum, Gellan gum were used in the formulations of gel. Prepared gels were evaluated for pH, rheological study, spreadability study, gelation, and gel melting study. At last Field Emission Scanning Electron Microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The first study by Goodson et al which demonstrated in vitro drug release for up to nine days [ 25 ]. Metronidazole is a broad-spectrum antibiotic and is active against most periodontal pathogens [ 26 ]. Minocycline is one of the most active antibiotics against most of the microorganisms associated with periodontal disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study by Goodson et al which demonstrated in vitro drug release for up to nine days [ 25 ]. Metronidazole is a broad-spectrum antibiotic and is active against most periodontal pathogens [ 26 ]. Minocycline is one of the most active antibiotics against most of the microorganisms associated with periodontal disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A comparative diffusion profile study between nanoemulsion and conventional macroemulsion has shown steady-state flux and better skin penetration of nanoemulsion than the surfactant-based emulsion system. 15 Optimized acyclovir nanoemulsion has also shown significantly better diffusion compared to conventional hot emulsification process based marketed formulation. All the results signify that the cold emulsification process is Each value is a mean of three determinations ± SD (n = 3).…”
Section: Formulation Characterizationmentioning
confidence: 99%
“…The specific makeup of these infections varies from person to person and, to some extent, from site to site on various teeth of the same topic. 2 Presently, more than 300 species of microbes have been identified in the oral cavity; however, only 5% of these are thought to be strongly linked to periodontitis, with 1% being present in more than 90% of occasions (Slots, personal interaction). Sadly, the identification of the disease's causative agents in humans has been hampered by the complexities of the flora, the sporadic nature of disease action episodes, and the comparatively wide variations in the data collected within and between subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Polyherbal gel represents a different strategy in the therapeutic and preventive management of oral and periodontal infections. 4 It has a wide range of therapeutic potencies, such as anti-inflammatory, antimicrobial, and antioxidant effects. Represent a different strategy for treating and preventing oral and periodontal infections.…”
Section: Introductionmentioning
confidence: 99%